Memory Functions in Recreational Pistol Sport Shooters: Does Lead Matter? - Sanna Asa-Mäkitaipale; Mervi Jehkonen; Jukka Uitti; Juhani Vilkki (SAGE Publishing, 2009)
Objective The aim of our study was to examine the memory functions of pistol sport shooters using powder charges when exposure to lead is expected to be considerably lower than in occupational circumstances. Methods A neuropsychological battery of memory and intelligence tests was administered to 20 sport shooters and 20 controls whose mean ages (SDs) were 55 (9.6) and 54 (9.3) years respectively. Memory functions were evaluated with three subtests of the Wechsler Memory Scale - Revised (WMS-R) and an incidental memory test. Intelligence was assessed with four subtests of the Wechsler Adult Intelligence Scale - Revised (WAIS-R). The level of alcohol consumption and depression were examined in both groups. Blood lead level was determined among the shooters. Results The shooters performed worse than the controls in the tests of incidental and logical memory. The groups did not differ in intelligence, mood or alcohol consumption. The mean (SD) blood lead level of the sport shooters was 0.52 μmol/L (0.40), responding 10.76 μg/dl (8.28). Conclusions Low lead exposure in recreational shooting conditions may impair verbal memory. Therefore it is important to ensure that lead exposure is prevented among those shooting for sport.